Teachers' conceptions about their profession: a qualitative approach to undergraduate level of a university - Daniel Eduardo García Suárez (Universitat Politècnica de València, 2015)
This article arises from research conducted in 2012 and 2013 on teachers' conceptions about the profession, learning, teacher professional development and research at the undergraduate level of a Colombian university known for its high academic quality.  This  texts  addresses  the  first category of such research, which deals with the conceptions of teachers about their  profession  from  a  qualitative study involving interviews with thirteen teachers selected with the help of a key informant who was provided with pre profiles. As a result, the characterization of the professional teacher, researcher and educator profile was obtained, and their understandings about the place of teaching in their professional activity was obtained, as well as their self-conception regarding  teaching,  time  conflict and dedication to teaching. This is of paramount importance when it comes to understanding the reasons why a teacher takes over their role in the university in a certain way and his epistemology about teaching.